Antifungal Effect of Oregano Essential Oil Against Penicillium expansum on Pyrus sinkiangensis - Qun Liu; Li Li; Zhenyuan Yang; Xiaodi Xiong; Qi Song; Baishu Li; Hang Zou; Lixiang Zhang; Tao Liu (Journal of Fungi)
Given the increasing demand for fruit safety assurance and environmental protection, plant essential oils have gained significant attention as natural alternatives for control of postharvest decay caused by various pathogens. In postharvest management, it is particularly important to effectively control postharvest decay without compromising the quality attributes of fruits. Although oregano essential oil (OEO) has been extensively studied for its antimicrobial properties against various postharvest pathogens, few studies have focused on its interactions with postharvest fruits. In this study, OEO was applied for management of postharvest decay of Pyrus sinkiangensis caused by Penicillium expansum, and its antifungal mechanisms and impacts on the quality attributes of pears were investigated. The OEO exhibited notable inhibitory effects, with determined MIC (0.02%) and MFC (0.04%) against P. expansum, which highlighted its potential as a viable alternative to synthetic fungicides. Our findings revealed that OEO disrupted P. expansum by compromising the integrity of the fungal plasma membrane, as evidenced by changes in plasma membrane permeability and the leakage of cellular components. The OEO treatment significantly reduced weight loss, maintained firmness, and preserved soluble-solid content in the treated pears. In addition, OEO treatment stimulated the intrinsic antioxidant mechanisms of pears, as demonstrated by elevated activities of superoxide dismutase and catalase during storage. This study provides compelling evidence for the antifungal and quality-preserving properties of OEO in the postharvest management of pears, underscoring its potential as an alternative to synthetic fungicides for controlling postharvest decay. The elucidation of the interaction between OEO and P. sinkiangensis would greatly enhance our comprehensive understanding of the biological activities of OEO and facilitate its practical application in the postharvest management of pears.